Continuing clozapine treatment after a diagnosis of cardiomyopathy. (9th September 2021) - Williams, F.; Lenihan, F.; Rowe, A.
Abstract : A patient in a medium secure psychiatric unit with a 19-year history of treatment-resistant schizophrenia and violence whose mental illness only responded to clozapine, was noted to have a sustained tachycardia. Echocardiography revealed mild biventricular cardiomyopathy. The patient was not significantly affected by this. Initial recommendation from Cardiology was to consider discontinuation of clozapine. It was decided, however, that the risk of worsening psychosis and resultant violence outweighed the risk of the patient's relatively mild cardiomyopathy. The patient was commenced on ramipril, and later bisoprolol. The patient no longer requires treatment in a medium secure unit and has remained on clozapine with follow-up from cardiology.